Mapping Cash Waqf Management and Development: A Systematic Literature Review of Research Trends, Themes, and Future Research Agenda - Dewi Atika; Lukmanul Hakim Siregar; Zulkarnaen Zulkarnaen; Muslim Marpaung; Rahmanta Rahmanta (Yayasan Rahmat Islamiyah, 2026)
This study aims to map the development of research on the management and development of cash waqf, identify the main themes, management approaches, development models, and prepare research gaps and future research agendas based on the synthesis of scientific literature. The research uses the Systematic Literature Review (SLR) approach with the stages of identification, screening, feasibility assessment, and literature synthesis following the PRISMA flow. Data was obtained from the Scopus database using keywords related to cash waqf management, cash waqf development, cash waqf innovation, Islamic philanthropy, and Islamic Social Finance. Based on the selection process, as many as 22 articles met the inclusion criteria and were analyzed thematically. The results of the study show that publications regarding cash waqf have increased significantly, especially since 2022. The research theme is dominated by governance, integration of Islamic Social Finance, institutional innovation, digitalization, sustainable development, financial inclusion, and economic empowerment. This study also identifies that the study of cash waqf is still dominated by case studies in certain countries, so a more comprehensive and cross-contextual research is needed. This research concludes that cash waqf has developed into a strategic instrument in the Islamic Social Finance ecosystem that requires professional, innovative, and sustainable governance. The research findings contribute in the form of mapping scientific developments, identifying research gaps, and preparing future research agendas that can be a reference for academics, regulators, and waqf management institutions in developing a more effective and sustainable waqf cash management system.